2009
DOI: 10.1007/s11999-008-0598-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anteversion Technique for Total Hip Arthroplasty

Abstract: Combined cup and stem anteversion in THA based on femoral anteversion has been suggested as a method to compensate for abnormal femoral anteversion. We investigated the combined anteversion technique using computer navigation. In 47 THAs, the surgeon first estimated the femoral broach anteversion and validated the position by computer navigation. The broach was then measured with navigation. The navigation screen was blocked while the surgeon estimated the anteversion of the broach. This provided two estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
365
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 402 publications
(382 citation statements)
references
References 31 publications
7
365
1
9
Order By: Relevance
“…This is quite a significant finding, as an unfavourable combined cup-stem alignment has a proven influence on the risk of impingement, the maximum range of motion, the extent of wear and dislocation or loosening [1,6]. According to our study data, cup and stem should be implanted at a defined combined anteversion [4]. Depending on gender, a combined anteversion of 25-35°f or men and 35-45°for women is desirable [12].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This is quite a significant finding, as an unfavourable combined cup-stem alignment has a proven influence on the risk of impingement, the maximum range of motion, the extent of wear and dislocation or loosening [1,6]. According to our study data, cup and stem should be implanted at a defined combined anteversion [4]. Depending on gender, a combined anteversion of 25-35°f or men and 35-45°for women is desirable [12].…”
Section: Discussionmentioning
confidence: 71%
“…Other authors have also demonstrated a relative anteversion variance when using a noncemented straight stem whose average anteversion was 16°, with a variance from 30°retroversion up to 45°a nteversion [4]. The relative scattering of the anteversion can be substantiated by the fact that the torsion of a noncemented straight stem due to press-fit anchoring is influenced by the individual structure of the femoral bone, the shape of the femur itself, femoral neck torsion and anterior bowing of the femur [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…The hemispheric reamer was only partially engaged in the acetabular bone. In 83 hips, femoral preparation was performed first to estimate the femoral stem anteversion and the cup anteversion was adjusted for a combined anteversion of 25°to 45° [10]. In 123 hips, the acetabulum was targeted to 20°to 25°of anteversion and prepared first.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, we only investigated patients using a single THA system. The uncemented femoral implants in this study tend to follow the normal anatomy of the proximal femur, limiting adjustability over stem orientation [25]. Secondly, the intended component positions of individual patients might be different.…”
Section: Discussionmentioning
confidence: 99%